In organello Protein Synthesis - Malgorzata Kwasniak-Owczarek; Hanna Janska (Bio-Protocol, 2014)
In organello protein synthesis method allows the analysis of mitochondrial translation products. The principle of this method relies on incubation of isolated intact mitochondria with radiolabeled amino acids such as 35S methionine. After protein synthesis, the radiolabeled translation products are subsequently separated by SDS polyacrylamide gel electrophoresis and analysed by autoradiography. For in organello analysis of protein synthesis, the isolated intact mitochondria must retain their bioenergetics capacity, and in consequence be fully functional and able to perform coupled respiration. This in turn requires a quick and gentle purification of mitochondria during their isolation.